PERANAN PUBLIC RELATIONS DALAM MENJAGA CITRA PERGURUAN TINGGI - Marisya Marisya; Nina Yudha; Ibrahim Besa (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Public Relations has a very fundamental role in developing the reputation oftertiary institutions. Higher education is also an organization that provideseducational services and also needs to manage its image. This will relate to publictrust in aspects of the quality of education and other fundamental componentsinherent in educational institutions. The problems in this paper is how the role ofpublic relations in maintaining the image of higher education. The results of thediscussion here are that PR for higher education institutions must know what theneeds of each of the public are. If then these needs are known, PR must conveythem to parties who can meet these needs so that if these needs can beaccommodated properly, it will lead to satisfaction for the public so that thepositive reputation of the organization can be achieved. PR in his job is to sellreputation. Selling reputation which is an accumulation of image is a form ofselling which can be said to be invisible directly even though it can be saidimplicitly but has a very large impact on an organization. In this case, universitypublic relations must be able to work together with any division in order toachieve the goal of achieving a positive reputation and image itself